Perspectives in clinical research on Azathioprine for steroid-dependent ulcerative colitis - Qu, Yuan-Ting; Ding, Jia-Yuan; Pan, Wei; Liu, Fang-Rui; Dong, Ai-Lian (Frontiers in Medicine, 2025)
This study explores the application of Azathioprine in the treatment of ulcerative colitis (UC) and the challenges associated with its long-term use. While short-term studies demonstrate the efficacy of Azathioprine in steroid-dependent UC, long-term data on its risks, including malignancies, infections, and chronic toxicity, remain insufficient. Furthermore, the impact of Azathioprine on patients’ quality of life over extended periods is still unclear. The research highlights the importance of optimizing Azathioprine dosing based on genomic data, particularly through TPMT and NUDT15 genotyping, to minimize adverse effects. However, further research is needed to develop individualized treatment strategies that can improve efficacy and reduce toxicity. The identification of predictive biomarkers, through genomics and proteomics, is likely to play a crucial role in improving treatment precision by identifying patients who are most likely to benefit from Azathioprine therapy. Additionally, combining Azathioprine with biologic therapies (such as anti-TNF agents or integrin inhibitors) and interventions targeting the gut microbiome may enhance the drug’s effectiveness while reducing reliance on steroids. Overall, large-scale clinical trials are urgently needed to evaluate the benefits and risks of these emerging therapies, ultimately supporting more personalized treatment approaches for steroid-dependent UC patients.